The Speech Styles Used by Female and Male Guests on The 20 Under 20 Podcast - Marcell Adrianus (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study explores the use of speech styles by the two of the guests in two podcast episode series released by Raymond Chin. The videos analyzed are titled “Omzet 3.5m per Bulan di Umur 19 Tahun?! Ft. Faiz- 20 Under 20 Episode 11” and “Bisnis Ratusan Juta Dulunya Di Cap “Gabakal Sukses” ft. Eva Alicia- 20 Under 20 Episode 4”. The two episodes of the podcast have two different guests, the female guest is Eva and the male guest is Faiz. Based on Baxter (2010) theory of speech styles, Baxter (2010) divides speech styles into two categories, the first of which is connected with female speech styles, namely: personal, compliant, polite, cooperative, and process-oriented. Second, male speech styles are connected with the following speech characteristics: matter-of-fact, assertive, aggressive, use of humor, ego-enhancing, and goal-directed. A descriptive qualitative approach was used by examining video transcripts to identify examples of speech styles. The findings reveal similarities in the use of speech styles between female guests and male guests, highlighting similarities in male and female speech styles features. This research concludes that the use of speech styles that are based on gender by Baxter is used by both of the guests, despite their gender. This research contributes to the understanding of speech styles in corporate communications and offers insights for future studies of speech styles in various business-related contexts.